Pattern Projection with a Sinusoidal Phase Grating. (13th May 2008) - Stoykova, Elena; Harizanova, Jana; Sainov, Ventseslav
Abstract : The aim of this work is to study the diffractive properties of a sinusoidal phase grating for incorporation as a pattern projection element in a multisource and multicamera phase-shifting profilometric system. Two challenges should be overcome for successful operation of such a system, which are connected to inherent limitations of the phase-shifting algorithm—requirements for a sinusoidal fringe profile and for equal background and contrast of fringes in the recorded patterns. As a first task, we analyze the frequency content of the projected fringes in the Fresnel diffraction zone for parallel and divergent light illumination at different grating parameters and wavelengths. As a second task, we evaluate the systematical errors due to higher harmonics and multiwavelength illumination. Finally, operation of the four-wavelength profilometric system is simulated, and the error of the profilometric measurement evaluated. The results of test measurements are also presented.